Pengaruh Fleksibilitas Kerja terhadap Kesejahteraan Mental Karyawan dengan Work Life Balance sebagai Variabel Intervening - Ragil Wahyu Dwi Ardani; Tamara Ajwa Salsabila Al Ahmad; Eko Wahyu Pujianto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of work flexibility on employee mental well-being with work-life balance as an intervening variable at CV. Nero Media. Work flexibility in this study refers to the freedom of time and place of work provided by the company to its employees. The method used is quantitative, with data collected through questionnaires distributed to 170 respondents who are active employees of CV. Nero Media. Data analysis was conducted using the Partial Least Square (PLS) approach to statistically examine the relationships between variables. The results show that work flexibility has a positive and significant effect on employee mental well-being, meaning that the higher the work flexibility, the better the employees' mental condition. Work-life balance also has a positive and significant effect on employee mental well-being, and is proven to partially mediate the effect of work flexibility on employee mental well-being. The R-Square value of 81.6% indicates that the research model has a strong predictive level for the mental well-being variable. This study recommends that CV. Nero Media strengthen its work flexibility policies, supported by management commitment, to sustainably improve employee mental health and productivity.